Conversion of fly ashes from different regions to mesoporous silica: effect of the mineralogical composition - Yilmaz, Muge Sari; Mermer, Nevin Karamahmut (SPRINGER, 2016)
This study reports the synthesis of mesoporous MCM-41 silica materials by the hydrothermal method using five different fly ashes from the Seyitomer (F-S), CatalagzA +/- (F-C), Tun double dagger bilek (F-T), Orhaneli (F-O), and AfAYinelbistan (F-A) power plants in Turkey. The mesoporous materials were not obtained from F-A which shows a lower Si/Al ratio and Si content. The synthesized MCM-41 samples from the other region fly ashes were characterized by X-ray diffraction, nitrogen adsorption-desorption, thermogravimetry, scanning electron microscopy, and high-resolution transmission electron microscopy analyses. The results demonstrated that the structural properties of the synthesized mesoporous materials were varied from depending on chemical compositions and mineral phase contents of the used fly ashes. Mesoporous silica MCM-41 was synthesized from different region fly ashes in Turkey. All synthesized sample except FOM have ordered hexagonal MCM-41 structure. Although the Si/Al ratio in the extracted solution of FOM was high, it has low Si content. The best quality MCM-41 sample was obtained from the extracted solution of FTM which has the highest Si/Al ratio and Si content. Taking these into account, Si/Al ratio and Si amount, and thereby mineral compositions of fly ashes play a significant role in the synthesis of mesoporous molecular sieves MCM-41. [GRAPHICS]
Keywords: MCM-41; Fly ash; Mineral composition; Alkaline fusion; MOLECULAR-SIEVES; TEMPLATE REMOVAL; ZEOLITE; Materials Science